Design of a transformable mobile robot for enhancing mobility. (18th January 2017) - Kim, Inho; Jeon, Wonseok; Yang, Hyunseok
This article proposes a design of a transformable mobile robot as a new concept of hybrid-type mobile robot in order to enhance mobility. Mobility considered in this work is based on stability, energy efficiency, and the capability to overcome obstacles. The proposed transformable mobile robot can change its bogie link lengths and wheel size. The relationships between mobility and the link length and the wheel size are studied. Its stability, energy efficiency, and the capability to overcome obstacles are compared through the simulations of three famous conventional passive bogie-type robots (Rocker-Bogie, RCL-E, and CRAB types) and the proposed robot. The simulation and experimental results show that the suggested transformable robot is superior to the conventional-type robots in terms of mobility enhancement.